The discursive construction of intersectionality in public policy implementation. - La Barbera, MariaCaterina; Cassain, Laura; Caravantes, Paloma (Critical Discourse Studies, 2024)
After three decades of intensive debate in academic and activist circles, intersectionality has progressively been adopted in public policies. Yet, the challenges of its application are still largely unexplored. This article adopts a discursive approach to study the process of policy implementation of an intersectionality-informed plan in Madrid City Council, Spain. The analysis of materials retrieved through interviews, a focus group, and participant observation enables us to explore how the technical staff interpret intersectionality and links it with other established approaches in equality and antidiscrimination law and policy, namely gender and diversity. We argue that preconceptions and positionality within the institutional structure deeply affect the interpretation of intersectionality and the subsequent action or non-action taken by implementing actors. Our study shows the challenges and opportunities to implement intersectionality in public policies that result from its discursive construction through the frames of gender and diversity.